2020
DOI: 10.1038/s41598-020-62789-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-thermal radiofrequency on body temperature in mice

Abstract: Communication technologies based on radiofrequency (RF) propagation bring great benefits to our daily life. However, their rapid expansion raises concerns about possible impacts on public health. At intensity levels below the threshold to produce thermal effects, RF exposure has also recently been reported to elicit biological effects, resembling reactions to cold. The objective of the present study was to investigate the effects of non-thermal RF on body temperature in mice and the related mechanisms. 3-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…This is consistent with suggestions that a thermal mechanism may be responsible for the effect of RF-EMF exposure on the sleep EEG [Danker-Hopfe et al, 2016]. Similarly, a thermal change was recently demonstrated in mice in response to daily exposure to 0.16 W/kg whole body average SAR, which was not present during the first exposure (and thus due to an indirect physiological change rather than dielectric absorption) [Mai et al, 2020]. It follows that low-level RF-EMF is sufficient to engage physiologically meaningful thermoregulatory changes, and provides indirect support for the view that the RF-EMF effect on the EEG may represent an 'indirect' response to exposure [Perentos et al, 2013].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with suggestions that a thermal mechanism may be responsible for the effect of RF-EMF exposure on the sleep EEG [Danker-Hopfe et al, 2016]. Similarly, a thermal change was recently demonstrated in mice in response to daily exposure to 0.16 W/kg whole body average SAR, which was not present during the first exposure (and thus due to an indirect physiological change rather than dielectric absorption) [Mai et al, 2020]. It follows that low-level RF-EMF is sufficient to engage physiologically meaningful thermoregulatory changes, and provides indirect support for the view that the RF-EMF effect on the EEG may represent an 'indirect' response to exposure [Perentos et al, 2013].…”
Section: Discussionsupporting
confidence: 91%
“…The possibility that the effect is mediated by direct activation of brain thermoreceptors (TRPM8) was tested in the above [Mai et al, 2020] study, where no support for this proposal was found. Although equivalent research has not been conducted in humans, and although there remains the possibility that different TRP receptors are involved, there is currently no evidence that direct activation of thermoreceptors by RF-EMFs is responsible for the above thermoregulatory changes.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it may correspond to non-shivering thermogenesis, which is a heat production mechanism in adipose tissues that contributes to mammals' thermoregulation during cold exposure. With the same exposure pattern to 900 MHz RF with an SAR of 0.16 W.kg -1 , we could confirm that after 4 days, body temperature in mice was shown to increase synchronously with RF exposure sessions, which also did not occur on the first days [Mai et al, 2020]. In these studies, the rodents' responses to RF were similar to those described for thermoregulation in cold conditions.…”
Section: Introductionsupporting
confidence: 72%
“…These non-thermal effects are also considered the most important from a medical point of view and are not covered by the established safety limits, because they are not directly measurable with a scientific instrument. This biophysical mechanism is defined as non-thermal if the interaction of the electromagnetic field with living material leads to specific effects that do not occur through the heating process (Glaser, 2005;Mai et al, 2020;Szasz et al, 2016). Non-thermal effects can be defined as biological effects resulting from a change in body temperature that is either less than 1°C or less than measurable or in the region of thermal noise (Scientific Committee on Emerging and Newly Identified Health Risks, 2015).…”
Section: Effects Of Radio Frequency Radiation On Human Healthmentioning
confidence: 99%